The use of transcutaneous bilirubin nomograms for the prevention of bilirubin neurotoxicity in the neonates - Lucia Casnocha Lucanova; Jana Zibolenova; Katarina Matasova; Katarina Matasova; Mirko Zibolen (Frontiers in Public Health, 2023)
PurposeAlthough neonatal jaundice is a ubiquitous and predominantly benign phenomenon, the risk of neurotoxicity exists in a number of infants with unconjugated hyperbilirubinemia. Plotting bilirubin values on nomograms enables clinicians to employ an anticipatory and individualized approach with the goal of avoiding excessive hyperbilirubinemia and preventing acute bilirubin encephalopathy and its progression to kernicterus. We aimed to construct nomograms for White term infants based on transcutaneous bilirubin (TcB) measurements using a JM-105 device.MethodsTcB measurements were taken in infants at ages ranging from 0 to 96 postnatal hours. We then constructed hour-specific TcB nomograms from forehead and sternum measurements in infants who did not require subsequent phototherapy.ResultsWe included 2,981 TcB measurements taken on the forehead and 2,977 measurements taken on the sternum in 301 White term newborn infants. We assessed the predictive abilities of the nomograms at six postnatal time intervals using receiver operating characteristic curves. The areas under the curves indicated reasonable prediction of hyperbilirubinemia requiring phototherapy, except for the forehead measurement taken within the first 12 h of life. Sensitivity tended to rise as postnatal age increased.ConclusionThe nomograms illustrate dermal bilirubin dynamics in White term neonates during the first 4 days of life. They may be useful tools to predict individualized risk of hyperbilirubinemia requiring treatment, and to plan optimal follow-up of infants at risk of bilirubin neurotoxicity.